Brucellosis: epidemiology, pathogenesis, diagnosis and treatment–a comprehensive review - Qureshi, Kamal A.; Parvez, Adil; Fahmy, Nada A.; Abdel Hady, Bassant H.; Kumar, Shweta; Ganguly, Anusmita; Atiya, Akhtar; Elhassan, Gamal O.; Alfadly, Saeed O.; Parkkila, Seppo; Aspatwar, Ashok (Annals of medicine (Helsinki), 2023)
Brucellosis is a pervasive zoonotic disease caused by various species. It mainly affects livestock and wildlife and poses significant public health threats, especially in regions with suboptimal hygiene, food safety, and veterinary care standards. Human contractions occur by consuming contaminated animal products or interacting with infected animals. This study aims to provide an updated understanding of brucellosis, from its epidemiology and pathogenesis to diagnosis and treatment strategies. It emphasizes the importance of ongoing research, knowledge exchange, and interdisciplinary collaboration for effective disease control and prevention, highlighting its global health implications. Pathogenesis involves intricate interactions between bacteria and the host immune system, resulting in chronic infections characterized by diverse clinical manifestations. The diagnostic process is arduous owing to non-specific symptomatology and sampling challenges, necessitating a fusion of clinical and laboratory evaluations, including blood cultures, serological assays, and molecular methods. Management typically entails multiple antibiotics, although the rise in antibiotic-resistant strains poses a problem. Animal vaccination is a potential strategy to curb the spread of infection, particularly within livestock populations. The study provides insights into the complex pathogenesis of brucellosis, the challenges in its diagnosis, and the management strategies involving antibiotic therapy and animal vaccination. It also highlights the emerging issue of antibiotic-resistant strains. In conclusion, brucellosis is a significant zoonotic disease with implications for public health. Efforts should be directed towards improved diagnostic methods, antibiotic stewardship to combat antibiotic resistance, and developing and implementing effective animal vaccination programs. Interdisciplinary collaboration and ongoing research are crucial for addressing the global health implications of brucellosis.